The Role of Human Resource Practices on Profits Generated by the Innovations: The Role of Top Management Support and Regularity of Employees Meetings - Sanja Pekovic; Maja Bacovic; Tatjana Stanovcic; Jelena Jovanovic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Previous scholars argue that human resource practices advance valuable knowledge what could be reflected positively on innovations. Accordingly, we empirically investigate whether human resource related practices such as top management support and regularity of employees meetings are related to profit generated by the innovation activities. Using survey data of Montenegrin firms, we find that firms in which top management supports employees' idea and have regular employees meetings related to innovation activities are likely to report higher profit generated by innovations. Therefore, our results underline the crucial role of human resource practices in the process of innovation that generates profitability for firms.
Keywords: O30; O15; 330; innovation; profit; human resource practices; top management support; meetings